Meta-Analisis Media Pembelajaran Audiovisual dalam Meningkatkan Keterampilan Menulis di Sekolah - Deden Hidayatullah (FKIP, Universitas Lakidende Unaaha, 2022)
The purpose of this study was to re-analyze the use of audiovisual learning media on writing skills. The method used in this research is meta-analysis. The research begins by formulating research problems, tracing relevant research results for analysis. Data were collected by searching electronic journals through Google Scholar with keywords in learning media, audiovisual, and writing skills. From the search results, 10 relevant articles that have been published in online journals were obtained. Descriptive qualitative method was used to analyzed the data. The analysis result suggested that audiovisual learning media can improve students’ writing skills. The audiovisual media can predict the writing performance ranging from the lowest 12.66% to the highest 80.5% with an average of 36.41%